"Forest and the trees: sociology as life, practice and promise" - "Johnson, Allan G." (Philadelphia, 2014)
If sociology could teach everyone just one thing, what would it be? The Forest and the Trees is one sociologist's response to the hypothetical-the core insight with the greatest potential to change how people see the world and themselves in relation to it. This Third Edition features: * Updated key references, data, resources, and examples, from global warming, Barack Obama's election, and gay marriage to the Occupy Wall Street Movement * A glossary of terms * A new framework for the short essays in Chapter 6, exhibiting the power of sociology to dig beneath easy and popular understandings * An additional analysis of how men$1 (Bs violence is made invisible even though most violence is perpetrated by men * Chapter 7$1 (Bs new focus on sociology as a worldview with an analysis of the origins of white privilege. ***Table of Contents***Acknowledgments** Introduction: Life, Practice, and Promise 1. The Forest, the Trees, and the One Thing 2. Culture: Symbols, Ideas, and the Stuff of Life 3. The Structures of Social Life 4. Population and Human Ecology: People, Space, and Place 5. Us, It, and Social Interaction 6. Things Are Not What They Seem 7. Sociology as Worldview: Where White Privilege Came From *Epilogue: Who Are We Really? *Notes *Glossary *Indexs
Keywords: Sociology